Helminthofauna Diversity in Synanthropic Rodents of the Emilia-Romagna Region (Italy): Implications for Public Health and Rodent Control - Filippo Maria Dini; Carlotta Mazzoni Tondi; Roberta Galuppi (Veterinary Sciences)
Synanthropic rodents are species well adapted to coexisting in anthropogenically influenced environments. This coexistence raises concerns about the potential risks of pathogen’s transmission due to their close proximity to human habitats. This study presents an epidemiological survey of the gastrointestinal helminth fauna in synanthropic rodents (Mus musculus, Rattus rattus, and Rattus norvegicus) from the Emilia-Romagna Region (Italy), aiming to provide updated data on the endoparasitic populations in these species. A total of 111 rodents, sampled from 2019 to 2021 during pest control programs, were examined for parasitic infections. Helminths were extracted through necropsy and microscopic analysis of gastrointestinal tracts and sediment, with species identification based on morphological characteristics. Overall, 72.1% of the rodents were found to be parasitized, with nematodes being the most prevalent. Syphacia muris, Aspiculuris tetraptera, Nippostrongylus brasiliensis, and Heterakis spumosa were the most frequently identified nematodes. Tapeworms, including Rodentolepis nana and Hymenolepis diminuta, were also detected, albeit in lower frequencies. The trematode Brachylaima recurva was recovered only in one R. rattus. Co-infection was common, particularly among rats, with 51.8% of black rats and 22% of brown rats harboring multiple parasitic species. Mice exhibited lower levels of polyparasitism, with only two individuals showing mixed infections. Interestingly, disparities between the detection of adult helminths and parasitic eggs were noted, especially in cases where no adults were observed, but eggs were found through sediment analysis. These findings suggest that traditional necropsy, especially with poorly preserved carcasses, may underestimate parasite prevalence. This highlights the importance of combining necropsy with microscopic techniques, such as flotation and sedimentation, for a more thorough assessment. Using these methods, nematodes with direct life cycles, such as Syphacia spp., Nippostrongylus brasiliensis, and Heterakis spumosa, have been confirmed as widespread and cosmopolitan among rodent populations. The detection of zoonotic parasites raises concerns about potential transmission to humans, particularly in areas with poor sanitation and high rodent densities. These findings underscore the need for integrated rodent control and environmental sanitation to reduce zoonotic risks.